Congenital Anterior Staphyloma in a Paediatric Patient: Clinical Presentation and Management Challenges - Nurhafizatul Akma Hasan; Noor Atikah Saini; Akmal Haliza Zamli; Wan Norliza Wan Muda; Norra Harun; Liza Sharmini Ahmad Tajudin (Malaysian Journal of Paediatrics and Child Health, 2026)
Congenital anterior staphyloma is a scarce condition characterised by the outpouching of anterior wall of the globe, typically involving both the cornea and sclera, leading to significant visual impairment. We report a seven-year-old boy, born prematurely at 34 weeks, who was diagnosed with congenital anterior staphyloma at birth. He had been monitored from an infant age and advised to undergo surgical intervention. However, surgery was delayed due to ongoing systemic illness, which required multiple hospital admissions, resulting in a lapse in follow-up care. The patient subsequently presented after sustaining an injury to the affected eye, which necessitated an emergency surgery. Following the procedure, an orbital implant was inserted, and he is now satisfied with his ocular prosthesis. In conclusion, congenital anterior staphyloma is a rare condition that presents at birth, requiring surgical intervention to improve cosmetic appearance and functional outcomes. Ongoing follow-up is essential for the unaffected eye to monitor associated ocular abnormalities.